A study of gender based discrimination on property rights in sri lanka: evaluation of applicability of relevant customary laws and government policies in the post-war context - Perera, A.C. (University of Jaffna, 2012)
Sri Lanka being a country with a mixed legal system, different groups of people in the country get governed by different set of personal laws; Kandyan, Muslim and Thesawalamai law. These laws contain discriminative provisions especially for women mainly in the areas of divorce, succession, and property rights. This study will only focus on land and property rights. These discriminatory laws and provisions were recently highlighted in the observations of the CEDAW committee report. These differences became more apparent when arranging resettlement process for the displaced families and reallocating land after the civil war and the Tsunami disaster. Most of these households are headed by women as men in the families had got either killed in the battle or disappeared. Most of these women have been prevented from acquiring ownership of these lands and accessing to other services as a result of the application of the head of the household concept in state administrative practices and also in some other instances because of the applicability of the said personal laws. Although this has become a major practical issue when reallocating lands and in the process of resettlement, it has not been addressed or discussed in the recent report of Lessons Learnt and Reconciliation Committee. This study will look at the possibility of a uniformity law and awarding joint ownership when allocating state lands and also abolishing the concept of Head of Household from state administrative practices.